Avaliação in vitro e in vivo da citotoxicidade e da genotoxicidade da solda de prata e da soldagem a laser utilizadas em ortodontia - Gonçalves, Tatiana Siqueira (2013)
In the present study, the cytotoxic and genotoxic effects of the silver solder and laser soldering used in Orthodontics were evaluated. For this, HepG2 e HOK cell lines were employed to evaluate the cytotoxicity (MTT reduction) and the genotoxicity (comet assay and cytokinesis block micronucleus cytome assay) of orthodontic bands containing or not silver soldered joints. Ionic metal release in the culture medium was verified by means of atomic absorption espectrophotometry. DNA effects on buccal mucosal cells of patients treated with Hyrax type expander appliances containing eight silver soldered joints were also evaluated through the buccal comet assay and the buccal micronucleus cytome assay. The in vitro cytotoxicity of orthodontic bands containing or not silver soldered or laser soldered joints was investigated and compared using the Saccharomyces cerevisiae model. Data obtained indicated that orthodontic bands suffer corrosion and are able to release ions to culture medium, being cadmium also detected in the samples evaluated. Silver soldered bands cause significant cytotoxic and genotoxic effects in mammal cells under in vitro conditions. The genotoxic effects are in part related to direct toxic effects and in part related to oxidative DNA damage. In humans, less intense genotoxic effects were observed. Laser soldering was less cytotoxic than silver soldering in in vitro conditions and should be more investigated since it seems to be a promising alternative to connect wires in Orthodontics.